Adopting hydrogen direct reduction for the Swedish steel industry: A technological innovation system (TIS) study. (1st January 2020) - Kushnir, Duncan; Hansen, Teis; Vogl, Valentin; Åhman, Max
Abstract: The Swedish steel industry stands before a potential transition to drastically lower its CO2 emissions using direct hydrogen reduction instead of continuing with coke-based blast furnaces. Previous studies have identified hydrogen direct reduction as a promising option. We build upon earlier efforts by performing a technological innovation system study to systematically examine the barriers to a transition to hydrogen direct reduction and by providing deepened quantitative empirics to support the analysis. We also add extended paper and patent analysis methodology which is particularly useful for identifying actors and their interactions in a technological system. We conclude that while the innovation system is currently focused on such a transition, notable barriers remain, particularly in coordination of the surrounding technical infrastructure and the issue of maintaining legitimacy for such a transition in the likely event that policies to address cost pressures will be required to support this development.